Fighting cytokine storm and immunomodulatory deficiency: By using natural products therapy up to now - Mohammed, Mona A. (Frontiers in Pharmacology, 2023)
A novel coronavirus strain (COVID-19) caused severe illness and mortality worldwide in 2022. As of this writing, 618 million cases have been diagnosed worldwide, with 6.55 million deaths. The number of deaths is closely connected to the growth of innate immune cells in the lungs, mainly macrophages, which generate inflammatory cytokines (specially IL-6 & IL-1β) that induce "Cytokine Storm Syndrome," multi-organ failure, and death. We focus on promising natural products and their biologically active chemical constituents as potential phytopharmaceuticals target in virus-induced proinflammatory cytokines since successful therapy for this condition is currently rare, and the introduction of an effective vaccine might take months. Blocking viral entrance and replication, as well as regulating humoral and cellular immunity in the uninfected population, are the most often employed treatment approaches for viral infections. Unfortunately, there is presently no FDA-approved medicine that can prevent or reduce SARS-CoV-2 access and reproduction. Until now, the most important element in disease severity has been the host's immune response's activation or suppression. Several medicines have been adapted for COVID-19 patients, including; arbidol, favipiravir, ribavirin, lopinavir, ritonavir, hydroxychloroquine, chloroquine, dexamethasone, antiinflammatory pharmaceuticals drugs such as tocilizumab, glucocorticoids, and anakinra (IL-1β cytokine inhibition) and siltuximab (IL-6 cytokine inhibition). However, these synthetic medications and therapies have a variety of side effects, including: heart failure, permanent retinal damage in the instance of hydroxyl-chloroquine, and liver destroy in the instance of remdesivir, among others. This review will summarize fighting cytokine storms and immunomodulatory deficiency by using natural products therapy up to now induced by COVID-19, as potential therapeutic measures to control cytokine storms.